A Performance Evaluation of WLAN-Femtocell-LTE beyond the Capacity Crunch. Does Femtocell have to overcome WLAN or can they coexist in HetNets? - Silva,K.C. (2016)
Abstract This paper originates from a practical experiment based on Mesh Networks. The promising results obtained from this experiment prompted us to discuss in greater depth whether Wireless Local Area Networks (WLAN) are still useful for current communications. This means that on the one hand femtocells can be defined as small base stations that use the same frequency bands as cellular networks. This has become a key feature in LTE to improve capacity and enhance data rates. On the other hand, WLAN, which in terms of infrastructure is similar to femtocells due to the IP backhaul network, seems to have outgrown its usefulness largely because it is being replaced by femtocell technology. In this paper, an attempt is made to clarify this uncertainty through an extensive analysis beyond the capacity crunch of both technologies. The work was undertaken by first working separately and in a second stage, working together to provide possible hybrid access to help offload traffic. Using cellular systems to underpin our research, we give examples of the capacity crunch for femtocells and WLAN through an extensive simulation campaign.